2015
DOI: 10.1002/jssc.201401262
|View full text |Cite
|
Sign up to set email alerts
|

Determination of fat‐soluble vitamins in vegetable oils through microwave‐assisted high‐performance liquid chromatography

Abstract: This article is protected by copyright. All rights reserved. AbstractIn this manuscript, a study of the effect of microwave radiation on the high-performance liquid chromatography separation of tocopherols and vitamin K1 was conducted. The novelty of the application was the use of a relatively low polarity mobile phase in which the dielectric heating effect was minimized to evaluate the non-thermal effect of the microwave radiation over the separation process. Results obtained show that microwave-assisted high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…This fact indicates that equilibrium conditions should have been reached inside of the HPLC column. Previous studies using microwave radiation to assist an HPLC separation also showed a similarthis trend (Carballo et al, 2015;Terol et al, 2012). It should be mentioned that, although the MW radiation was quickly absorbed by the mobile phase, moderate heating inside of the column was produced in this application.…”
Section: Optimisation Of the Mw-hplc-elsd System For Separation Of Tgssupporting
confidence: 55%
See 3 more Smart Citations
“…This fact indicates that equilibrium conditions should have been reached inside of the HPLC column. Previous studies using microwave radiation to assist an HPLC separation also showed a similarthis trend (Carballo et al, 2015;Terol et al, 2012). It should be mentioned that, although the MW radiation was quickly absorbed by the mobile phase, moderate heating inside of the column was produced in this application.…”
Section: Optimisation Of the Mw-hplc-elsd System For Separation Of Tgssupporting
confidence: 55%
“…170 W. However, the column did not wholly absorb the radiation. Therefore, to avoid magnetron damage, a water container (2100 mL total volume) at a temperature of 20 ºC was placed inside the oven as a radiation well (Carballo et al, 2015) (Carballo, Prats, Maestre, & Todolí, 2015). Furthermore, an optimisation study was performed to select both the 300 S ELSD spray chamber and drift tube temperatures.…”
Section: Chromatographic Conditions Of Hplc-elsdmentioning
confidence: 99%
See 2 more Smart Citations
“… made a 20‐fold dilution of 40 mg oils in tetrahydrofuran/acetonitrile (4:6, v/v), Carballo et al. made a 1:10 v/v dilution with propan‐1‐ol. Moreover, QuEChERS was also applied for VE extraction.…”
Section: Introductionmentioning
confidence: 99%